The analysis of return policy in the UK based on scorecard - XU, YANING (2019)
The return policy is a vital part of every retailer. Consumers may return the product for a variety of reasons, such as product colour or size error, poor functionality, damage during shipping, or regret the impulse of purchase. This study aims to find what is a good or poor return policy, and the ‘dimensions’ or ‘attributes’ where return policies can differ. Moreover, the research tries to show the current status of the UK return policy in different sectors. Finding which areas perform excellently; they have a lenient return policy or a strict one. The work researched 50 companies in various industries in the UK. The scorecard is used to analyse the six characteristics of the return policy, namely time window, refund mechanism, scope, effort, exchange and location. As a result, each company had a score in each characteristic. The findings show that return policy in different industries has different features, and they perform differently in six characteristics. However, there are also some limitations. The number of companies selected is limited, and the scorecard exists some subjective idea. Moreover, it only researches the return policy in the UK. However, there is less literature related to the characteristics of the return policy, relationships between characteristics and return policy and the difference of return policy in different sectors. These findings can make contributions to the works of literature in this area.